Translational Neurodegeneration - Ding, Jianqing; Tan, Yuyan; Shengdi, Chen
Translational Neurodegeneration is an open access, peer-reviewed journal that covers research, therapeutics and education for all aspects of neurodegenerative diseases. By offering a high-visibility forum for new insights and discussions, Translational Neurodegeneration creates a novel interface between the fields of basic, translational, and clinical research. It includes Parkinson's disease and movement disorders, Alzheimer's disease and other dementias, motor neuron disease and other neurodegenerative diseases. Topics of interest include but are not limited to the following areas of neurodegenerative diseases: Epidemiology and pathogenesis Research into diagnosis and prevention Research into the disease pathogenesis Development of new drugs and cell therapy Drug delivery Rehabilitation Translational Neurodegeneration offers the opportunity for scientists, clinicians and physician-scientists to publish their research and clinical trials in a journal which is applicable to their specific field.